Migration from the Guatemalan scientific literature:state of the art, years 2011-2020 - Bámaca-López, Efraín (2022)
The objective of this article is to analyze the scientific production published in Guatemala on migration, between 2011 and 2020, in order to establish a starting point towards a new path in national research. For this purpose, the journals with topics related to the social sciences and humanities, hosted in the Portal de Revistas de Guatemala of the Universidad de San Carlos de Guatemala, were used as a frame of reference, resulting in the review a total of 1030 scientific articles. Finally, it opens the debate for some new lines of research that have emerged based on the world situation on human mobility in general and especially in Guatemala